Methotrexate for Severe Childhood Atopic Dermatitis: Clinical Experience in a Tertiary Center. Issue 5 (21st July 2017) - Dvorakova, Veronika; O'Regan, Grainne M.; Irvine, Alan D.
Abstract: Background/Objectives: Atopic dermatitis (AD) affects up to 20% of children. Although the majority of patients are adequately controlled using emollients, topical corticosteroids, topical calcineurin inhibitors, or phototherapy, children with moderate to severe AD may require systemic treatment for control. The objective of the current study was to evaluate the efficacy and safety of methotrexate in children with severe AD attending a tertiary referral center. Methods: A retrospective chart review was undertaken of all children who received methotrexate for severe AD at our tertiary referral center from November 2010 to August 2015. Results: Forty‐seven children were started on methotrexate for AD during this period. The mean Investigator Global Assessment (IGA) at the 3‐ to 5‐month follow‐up improved from 4.25 to 2.8, with further improvement to 1.9 in the patients that continued therapy beyond 10 months. Changes in the Children's Dermatology Life Quality Index (CDLQI) mirrored changes in the IGA, with improvement in the mean CDLQI from 14.4 at the start of the treatment to 7.5 at the 3‐ to 5‐month follow‐up. Further improvement in the CDLQI to 6.6 in patients who continued methotrexate beyond 10 months confirmed continued improvement in disease control beyond medium‐term therapy. The treatment was well tolerated. Conclusions: Methotrexate appears to be an effective, safe treatment for severe pediatric AD. Its therapeutic effects continue beyond the medium‐term treatment period, as reflected by further improvement in IGA and CDLQI scores in patients who continued methotrexate therapy beyond 10 months.